Jacket Structure Design Optimization to Reach Minimum Construction Cost - Aufar Syahmi Faris Sumardi; Daniel Mohammad Rosyid (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Offshore jacket structures are essential components in platform construction, requiring optimization due to high material, fabrication, and coating costs. The objective of this research is to achieve cost-effective designs without compromising safety. The methodology employs Sequential Quadratic Programming (SQP) with a surrogate-based approach to optimize structural dimensions, while reliability is assessed using Monte Carlo Simulation to account for uncertainties. Optimization conducted in MATLAB resulted in significant improvements in the dimensional reduction of most design variables, including a 20.32% reduction in total construction costs. Material, fabrication, and coating costs decreased by 19.05%, 28.11%, and 6.14%, respectively. The reliability index (Beta) of critical members improved to a range of 3.12–3.29, exceeding the safety threshold of 3.09.